Analisa Percepatan Proyek Gedung Sekolah SMK Multi Masmur Pekanbaru (Study Kasus : Gedung Sekolah SMK Multi Masmur Pekanbaru Riau - Kaharuddin Kaharuddin; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Making a plan and schedule for the project always refers to the condition of assumptions and forecasts that existed at the time plans and schedule are made, therefore the problem will arise if there is a discrepancy between the forecasts and assumptions with actual reality. Delays in construction project often occurred and give some disadvantages for everyone, both the contractor and the employer. Therefore, the problem will arise when assumption different from the reality in field. Delays of the project will cost high penalties the contractor. SMK Multi Masmur Pekanbaru construction projects has delayed with in 15 day calendar from the duration the project in the contract. Delayed in the project should be tackle with accelerating the time in remaining activities. The acceleration of the work can the be done in two ways, firsly, overtime working and secondly is by adding additional labors and equipments. Performed analsis focus on the job experience in critical line. Then the result of delaying cost Rp 32.942.781,-. The cost needed if accelerated from overtime working is Rp 41.449.497,- and Rp 17.407.500,- for adding the employers and the equipments. The best alternative solution is the additional tool and labors. Total acceleration in 13 days completed with the time and cost efficient.Keyword : contruction delay, contruction cost, duration shortening, equipment and workers addition.